Public-Private Partnership and Policy Implementation in the Greater Port Harcourt City Development Authority, 2009–2025 - ThankGod Nwafor (JOURNAL OF PUBLIC ADMINISTRATION AND SOCIAL WELFARE RESEARCH, 2026)
The persistent problem of policy implementation failure in Nigeria, where many development plans remain poorly executed despite substantial policy formulation efforts have become a huge source of concern. The Greater Port Harcourt Master Plan was designed to promote sustainable urban development through collaboration between government and private sector actors, particularly in addressing infrastructure deficits, urban renewal, and service delivery challenges. However, implementation has been constrained by bureaucratic inefficiencies, regulatory uncertainties, and limited resource availability. This study examined Public-Private Partnership (PPP) and policy implementation in the Greater Port Harcourt City Development Authority (GPHCDA), Rivers State, from 2009 to 2025. The study adopted a correlational research design, data was collected from 360 staff members of the GPHCDA using Likert scale structured questionnaire. Collected data were analyzed using descriptive statistics, while Pearson’s product moment correlation was used to test hypothesis at a 0.05 level of significance. Findings revealed that public-private partnership has a moderate-to-high extent of influence on policy implementation in GPHCDA. The hypothesis testing indicated a strong and statistically significant relationship between PPP and policy implementation (r = 0.820, p < 0.05). This implies that increased collaboration between public and private sectors significantly enhances policy execution, infrastructure delivery, and urban development outcomes. The study concluded that PPP is a critical mechanism for bridging resource gaps and improving the effectiveness of policy implementation in the Greater Port Harcourt City project. However, challenges such as corruption risks, regulatory bottlenecks, and exclusion of vulnerable groups were identified as limiting factors. Accordingly, the study recommends that the Rivers State should focus on strengthening institutional frameworks and accountability systems was recommended to ensure sustainable urban development outcomes in the GPHCDA.